2022
DOI: 10.1021/acs.jpcc.2c04313
|View full text |Cite
|
Sign up to set email alerts
|

Research on Circularly Polarized Luminescent and Clustering-Triggered Emission Properties of Cholesteryl Benzoate

Abstract: Circularly polarized luminescence (CPL) materials have attracted intensive attention due to their exceptional photophysical properties. However, it has been rarely reported in the field of nontraditional luminescence. It is of great significance to construct circularly polarized luminescent materials with atypical luminescent groups without traditional conjugated structures. Cholesteryl benzoate is a classical cholesteric liquid crystal, and we coincidentally find that it shows clustering-triggered emission be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 36 publications
0
5
0
1
Order By: Relevance
“…According to our previous research findings, cholesteryl benzoate show clustering‐triggered emission characteristics, including concentration‐enhanced emission, aggregation‐induced emission, excitation wavelength dependence, and phosphorescent property. [ 39 ] By combination of experiments and theoretical calculations, it was confirmed that the cholesterol group is cluster chromophore. When aggregated, the energy gap between HOMO‐LUMO of cholesteryl benzoate is reduced, so as the aggregation degree increases, its emission wavelength gradually red‐shifts.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to our previous research findings, cholesteryl benzoate show clustering‐triggered emission characteristics, including concentration‐enhanced emission, aggregation‐induced emission, excitation wavelength dependence, and phosphorescent property. [ 39 ] By combination of experiments and theoretical calculations, it was confirmed that the cholesterol group is cluster chromophore. When aggregated, the energy gap between HOMO‐LUMO of cholesteryl benzoate is reduced, so as the aggregation degree increases, its emission wavelength gradually red‐shifts.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, according to our previous research, cholesterol exhibits clustering‐triggered emission (CTE) characteristic and phosphorescent property. [ 39 ] In principle, cholesterol can also emit CPRTP after being excited, and the phosphorescence emission wavelength will be changed with the excitation wavelength. Therefore, strong and multicolor‐tunable pure organic CPRTP cholesteric liquid crystal will be obtained.…”
Section: Introductionmentioning
confidence: 99%
“…2.1 自组装胆甾型有机圆偏振室温磷光材料 簇触发发射(clustering-triggered emission,CTE) 常表现出浓度增强发射、 聚集诱导发射和激发波长依 赖性的特性 [30] 。手性胆固醇苯甲酸酯不仅可以形成 CLCs,还具有簇触发 CPL 的性能 [31] 。2023 年,Zhang Hailiang 课题组制备了含有胆固醇簇光发色基团的 CPL 薄膜 [32] 。通过改变激发波长,实现了 CPL 信号 的动态调节(glum 值高达 0.1) [33] 。由于引入两 个长寿命激发态,Chol-C6-DF 表现出双磷光发射行 为。在 380 nm 光源激发下,发射来源于二苯并呋喃 基团的黄色 RTP(gPh = -0.19;寿命τ = 567.7 ms) ;在 [33] .…”
Section: 胆甾型有机圆偏振室温磷光材料unclassified
“…In our previous research, we found that cholesterol showed CTE characteristic. [41,42] PM6Chol comprise cholesterol group, which is expected to exhibit CTE property. And then we conducted a detailed exploration of the photophysical properties of the PM6Chol.…”
Section: Photophysical Properties Of Polymer In Solutionmentioning
confidence: 99%
“…In our previous research, we discovered that cholesteryl benzoate also demonstrated clustering‐triggered luminescence. [ 42 ] Moreover, within its cholesteric phase regime, it retained its helical liquid crystal structure, allowing for the acquisition of CPL through CTE. However, the g lum was only −2.6 × 10 −3 , and could not meet practical application requirements.…”
Section: Introductionmentioning
confidence: 99%